Built environment perceptions: How older people decode outdoor public spaces - Figueiredo, M.; Eloy, S.; Marques, S.; Dias, L. (27th IAPS Conference: Global challenges, local impacts: Rethinking governance, sustainability and consumption in light of climate change: Book of abstracts, 2022)
When UN released the “Global Age Friendly Cities: A Guide” in 2007, the concern around ageing people and their needs was evident. As the world ages, the built environment requires special attention in order to assist this growing part of the society. An age-friendly city demands an inclusive design that includes e.g. green spaces, safe pavements and safe pedestrian crossings. Also, mobility in cities and new forms of transport as bicycles and electrical scooters demand the update of urban design guidelines and urban policies. The goals of this study are to provide an overview of existing literature regarding emotions and perception from older people related to the exterior built environment by mapping these publications according to several criteria.